Alveolar soft-part sarcoma of the oral cavity: A review of literature. (December 2018) - Shelke, Pankaj; Sarode, Gargi Sachin; Sarode, Sachin Chakradhar; Anand, Rahul; Prajapati, Ghevaram; Patil, Shankargouda
An alveolar soft-part sarcoma is a malignant neoplasm primarily affecting the soft tissues of head and neck. The aim of the present review is to systematically present the demographic and clinico-pathological data of articles published in the English medical literature. A comprehensive search of the databases (PubMed, Medline, SCOPUS, Web of Science, and Google Scholar) along with cross references to the published articles on alveolar soft-part sarcoma for eligible studies/case reports published since 1957 till date was done to retrieve the data. A total of 74 cases were identified and analyzed from 42 papers published in the English medical literature. All the clinical, radiographic, and prognostic features were analyzed and presented along with the treatment strategies. Alveolar soft-part sarcoma is a rare and aggressive malignancy of uncertain histologic origin with a propensity for vascular invasion and distant metastasis. This neoplasm requires careful clinical, radiographic, and histopathologic evaluation to reach to the correct diagnosis.